(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Patient satisfaction survey is one of the crucial tasks, playing a significant role in improving the quality of diagnosis and treatment at the National Lung Hospital (NLH). Objective: To assess the level of inpatient satisfaction and propose intervention solutions to enhance the quality at NLH in 2023. Methods: Cross-sectional descriptive study, surveying 832 inpatients treated at 13 Clinical Departments at NLH, from March 2023 to December 2023. Results: The survey results help find issues where patients are not really satisfied/the level of satisfaction is not high: Food quality, daily menu changes, signage, advice on medication regimen... provide a basis for timely intervention solutions, increasing the satisfaction of patients and their families.